The impact of pulse timing on cortical and subthalamic nucleus deep brain stimulation evoked potentials - Campbell, Brett A.; Favi Bocca, Leonardo; Escobar Sanabria, David; Almeida, Julio; Rammo, Richard; Nagel, Sean J.; Machado, Andre G.; Baker, Kenneth B. (Frontiers in Human Neuroscience, 2022)
The impact of pulse timing is an important factor in our understanding of how to effectively modulate the basal ganglia thalamocortical (BGTC) circuit. Single pulse low-frequency DBS-evoked potentials generated through electrical stimulation of the subthalamic nucleus (STN) provide insight into circuit activation, but how the long-latency components change as a function of pulse timing is not well understood. We investigated how timing between stimulation pulses delivered in the STN region influence the neural activity in the STN and cortex. DBS leads implanted in the STN of five patients with Parkinson’s disease were temporarily externalized, allowing for the delivery of paired pulses with inter-pulse intervals (IPIs) ranging from 0.2 to 10ms. Neural activation was measured through local field potential (LFP) recordings from the DBS lead and scalp EEG. DBS-evoked potentials were computed using contacts positioned in dorsolateral STN as determined through co-registered post-operative imaging. We quantified the degree to which distinct IPIs influenced the amplitude of evoked responses across frequencies and time using the wavelet transform and power spectral density curves. The beta frequency content of the DBS evoked responses in the STN and scalp EEG increased as a function of pulse-interval timing. Pulse intervals less than 1.0ms apart were associated with minimal to no change in the evoked response. IPIs from 1.5-3.0ms yielded a significant increase in the evoked response, while those greater than 4ms produced modest, but non-significant growth. Beta frequency activity in the scalp EEG and STN LFP response was maximal when IPIs were between 1.5-4.0ms. These results demonstrate that long-latency components of DBS-evoked responses are predominantly in the beta frequency range and that pulse interval timing impacts the level of BGTC circuit activation.